Long-Term Outcome after Joint Bleeds in Von Willebrand Disease Compared to Haemophilia A: A Post Hoc Analysis - van Galen, Karin P. M.; Timmer, Merel; de Kleijn, Piet; Leebeek, Frank W. G.; Foppen, Wouter; Schutgens, Roger E. G.; Eikenboom, Jeroen; Meijer, Karina; Fijnvandraat, Karin; Laros-van Gorkom, Britta A. P.; Twisk, Jos W.; Mauser-Bunschoten, Eveline P.; Fischer, Kathelijn; on behalf of the WiN Studygroup (Thrombosis and Haemostasis, 2018)
Long-term outcome after joint bleeds in von Willebrand disease (VWD) (von Willebrand factor activity ≤ 30 IU/dL) could differ from moderate or severe haemophilia A (HA) (factor VIII [FVIII] 1–5 IU/dL or FVIII < 1 IU/dL). We performed a post hoc analysis on Haemophilia Joint Health Score (HJHS, 0–124), X-ray Pettersson scores (PS, 0–13/joint) and the Haemophilia Activities List (HAL, 0–100), using multivariable regression to adjust for age (rate ratio [RR] or odds ratio [OR] [95% confidence interval]). We included 48 VWD (median age, 47 years, type 3 VWD, n = 19), 39 moderate HA (median, 39 years) and 59 severe HA patients (median, 25 years) with documented joint bleeds. VWD patients suffered repeated bleeding (lifetime > 5/joint) less often than moderate and severe HA patients (52% vs. 77% vs. 98%). HJHS and PS in VWD were similar to moderate HA (median HJHS 5 vs. 6, RR 0.9 [0.5–1.4] and PS > 3 of ≥ 1 joint OR 0.3 [0.1–1.4]), but better than in severe HA patients (median HJHS 5 vs. 9, RR 1.8 [1.1–2.9]; PS > 3 in any joint OR 0.1 [0.0–0.3]). Self-reported limitations in activities were comparable across VWD, moderate HA (HAL score < 95: 67% vs. 49%; OR 1.4 [0.5–3.6]) and young adults with severe HA (67% vs. 48%; OR 1.7 [0.7–4.4]). Despite fewer joint bleeds, joint outcome after joint bleeds was similar in VWD and moderate HA patients. Type 3 VWD patients had worst joint outcome, comparable to younger intensively treated severe HA patients. Limitations in activities occurred as often in VWD as in both moderate and severe HA.
Keywords: von Willebrand disease; joint bleed; arthropathy; haemophilia A; HJHS; Pettersson; HAL